HYDRODYNAMIC MODEL FOR A β Cephei VARIABLE BW Vulpeculae - Fokin, A.; Mathias, Ph.; Chapellier, E.; Gillet, D.; Nardetto, N. (Одеські астрономічні публікації, 2017)
A hydrodynamical model for the high-amplitude β Cephei star BW Vulpeculae is generated, and the spectral line profiles are calculated for different pulsational phases. The pulsational characteristics and line profiles are compared with recent observational data obtained during seven consecutive nights in August 2000. We found a generally good agreement in the basic photometric and spectral parameters. Two strong shock waves appear during one period, and the "stillstand" is due to the gas dynamics between the passages of these shocks. Note that this good agreement suppose a metallicity Z=0.03, while a metallicity Z=0.02 does not lead to the correct amplitudes and shapes of the curves.